Proyecto de factibilidad para la creación de una empresa productora y comercializadora de crema de aguacate (mascarilla) en la ciudad de Cayambe, canton Cayambe, provincia de Pichincha - GIOVANNI ALEXANDER, OLMEDO HEREDIA (2017)
The present feasibility study for the creation of a company producing and marketing avocado cream was carried out to establish the positive and negative aspects that will influence the implementation of the company of avocado creams, among the most important findings of each study the following could be determined. The general objective of the present work is to elaborate a feasibility project for the creation of a company producing and selling avocado cream (mask) in the City of Cayambe, which allows to favor local commerce, the use of labor and constant production and marketing of new innovative products to meet the needs of people The methods used for the development of this research; Inductive method allowed to determine the general conclusions of the project; Deductive method provided market information to determine the sample size, based on general and actual population data at the local level; Descriptive Method was used in the drafting of the project, especially regarding the rational interpretation and the objective analysis of the facts and Statistical Method allowed to determine numerical data and a real quantitative analysis that provided the market study. The techniques of study applied; direct observation within the technical study to establish the location of the company and the survey with data collection, organization and tabulation was presented the information obtained, which allowed in this way to analyze the results, in addition was made market segmentation for research proposal, estimating a representative sample of 394 surveys. Situational diagnosis carried out in the city of Cayambe, specifically to the agricultural sector dedicated to the production of avocado, which are located in its environs of the city, it was determined that there is sufficient raw material that can be used by the project, there will be no shortage in the place. The market study allowed to know the characteristics of the target market of the product, as well as the opportunity to introduce the product in the city of Cayambe, with respect to the offer, completely covers the expectations of the consumers, therefore, it is foreseen a success in the activity, was determined the Potential Demand Study with 90.36% resulting in 20486 women, Real Demand with 92.13% resulting in 18874 women, Per Capita Average Annual Consumption per woman of 17 , 29 avocado creams and effective Demand with 90.55% results in 295495 women and the study of the Offering results in 3480 units annually and finally the Unsatisfied Demand that calculated the difference between the effective demand and the offer as a result 292015 The technical study established that the strategic location for the implementation of the company is in the city of Cayambe, Parish La Patarata, Av. Natalia Jarrin, because there are adequate conditions for the operation, it defined the operational aspects that the project to be efficient in the elaboration and commercialization of the product. The analysis of the financial study determined that the optimum investment to start the project amounts to $ 57,575.37, as well as their respective income, expenses, financial statements and financial evaluation with the application of indicators that measure the value of money in time yielding results that demonstrate the feasibility of the project in the sector. Carrying out the financial evaluation indices, it was determined that for the calculation of the NPV applicable to the project an investment rate of 12.11% was used, which generated a net present value greater than zero that is positive; therefore, the project would be acceptable, generating profits of $ 211,768.36 over the 10 years of useful life. From the result obtained it was concluded that the benefit-cost ratio for the project is greater than 1, therefore the project execution is financially acceptable, which means that for every dollar invested USD will be obtained. 0.40 cents of profit. With the period of recovery of the capital was determined the time in which the investment will be recovered. According to this we find that the investment will be recovered in its entirety in 1 year, 1 months and 20 days, being an acceptable time; because it is within the life of the project. The IRR of the project is 87.26%; This is considered to be greater than the market opportunity rate (12.11%), which ratifies the feasibility of the project. For the present project, the sensitivity values are less than 1, therefore they do not affect the changes in the increase of the costs and the decrease in the income; that is, the project is not sensitive to these changes as demonstrated in the calculation. For administrative and operational management qualified and competitive human talent will be hired to ensure efficiency and efficiency in the activities and thus obtain concrete results, both in the administrative and operational tasks carried out in the company. Finally, we implanted the conclusions that emerged throughout the research, to give concrete satisfactions to the research work and also presented the recommendations that will be of vital importance in order to reach an improvement and sustained growth in the company producing avocado creams.